Kajian Penerapan Sistem Informasi Pelayanan Pajak Reklame (Studi Kasus : Suku Dinas Pelayanan Pajak di Provinsi DKI Jakarta) - Sulistiyah Sulistiyah (LPPM STMIK ANTAR BANGSA, 2017)
ABSTRACT - The successful application of information technology is very dependent on the acceptance of these technologies by the user as the user. This study entitled